Visitors' Subjective Well Being: The Effect of the Motivational Sharing Travel Photos Through Instagram - Zikri, Muhammad Afdhal; Weldy, Arif Syafri; Ananda, Elviona Rizky; Ferdian, Feri (Institut Pariwisata dan Bisnis Internasional, 2023)
Social media is a place where users can exchange information with fellow users, one of the information obtained is about tourism. In today's digital era, social media such as Instagram has become a popular platform for users to share their travel moments. By using social media one can find out a lot of information and reviews from visitors who have experience in tourism travel, so that they have considerations and decisions in visiting tourism places. The purpose of this study was to examine the effect of motivation to share photos on Instagram on visitors' experiences of subjective well-being in the tourism object of Air Manis Beach, Padang City. The study used a quantitative with a causal associative approach. The data was obtained by distributing questionnaires online through Instagram users who have shared photos of their experiences visiting the tourism object of Air Manis Beach, Padang City. So that as many as 184 people were obtained, with a Likert scale. The data analysis technique used the Partial Least Square Structural Equation Modeling. The results found that recognition and status, enjoyment, and disclosure influenced visitors' experiences of subjective well-being in the tourism object of Air Manis Beach, Padang City. Meanwhile, tourism information did not affect visitors' experiences of subjective well-being in the tourism object of Air Manis Beach, Padang City. This study concluded that when people share motivational and inspiring travel photos via Instagram, they can feel an increase in subjective well-being.